2015
DOI: 10.1128/jvi.00783-15
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Individual or Combinations of Broadly Neutralizing Antibodies and Antiviral Reagents against Cell-Free and Cell-to-Cell HIV-1 Transmission

Abstract: To date, most therapeutic and vaccine candidates for human immunodeficiency virus type 1 (HIV-1) are evaluated preclinically for efficacy against cell-free viral challenges. However, cell-associated HIV-1 is suggested to be a major contributor to sexual transmission by mucosal routes. To determine if neutralizing antibodies or inhibitors block cell-free and cell-associated virus transmission of diverse HIV-1 strains with different efficiencies, we tested 12 different antibodies and five inhibitors against four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
44
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 82 publications
2
44
0
Order By: Relevance
“…bNAbs directed to the MPER have low efficacy against VSmediated viral transmission, even though they potently neutralize cell-free virus (19,(33)(34)(35)(36). To examine the role of the MPER in cell-free infection and cell-cell viral spread, an assay was developed to compare the spread of two well-characterized HIV-1 AD8 MPER mutants, W666A and I675A (Fig.…”
Section: Cell-associated Mper Mutant Viruses Retain the Ability To Inmentioning
confidence: 99%
See 2 more Smart Citations
“…bNAbs directed to the MPER have low efficacy against VSmediated viral transmission, even though they potently neutralize cell-free virus (19,(33)(34)(35)(36). To examine the role of the MPER in cell-free infection and cell-cell viral spread, an assay was developed to compare the spread of two well-characterized HIV-1 AD8 MPER mutants, W666A and I675A (Fig.…”
Section: Cell-associated Mper Mutant Viruses Retain the Ability To Inmentioning
confidence: 99%
“…For example, VS-mediated viral transmission is less sensitive to commonly used nucleoside reverse transcription inhibitors such as nevirapine, zidovudine, and tenofovir (29 -32). Importantly, VS-mediated HIV-1 transmission between CD4 ϩ T cells and between HIV-1-infected MDMs and uninfected CD4 ϩ T cells is less sensitive to neutralization by bNAbs, when compared with cell-free virus infections, indicating that this mode of spread may represent an obstacle to successful vaccine development and neutralizing antibody therapy (19,(33)(34)(35)(36). Although these differences between cell-to-cell and cell-free virus transmission can be explained in part by a higher local multiplicity of infection at the VS, it is also plausible that cell-free and cell-associated viruses possess structural differences that confer distinct functional advantages to the two viral forms.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Cell-to-cell infection is mediated by adhesive cell-cell contacts that form between infected and uninfected CD4 ϩ T cells (called "virological synapses" [VS]). Cell-to-cell infection through VS is more efficient than cell-free infection in vitro (1,2) and has been found to resist neutralizing antibodies (NAbs) to a greater extent than infection by the same viral clone when it is presented as cell-free virus (1,(3)(4)(5)(6)(7)(8)(9)(10)(11).…”
Section: Importancementioning
confidence: 99%
“…Even a slight decrease in susceptibility in vivo could result in a substantial effect on virus production in amplification over multiple rounds of replication. Studies have consistently shown that HIV-1 broadly neutralizing antibodies can block cell-to-cell infection but that much higher concentrations or bnAb combinations are frequently required (33)(34)(35)(36)(37). All of those studies reported that differences between cell-free neutralization and cell-associated neutralization were seen across virus strains and antibody epitopes.…”
mentioning
confidence: 99%